Fanzor is a eukaryotic programmable RNA-guided endonuclease - Saito, Makoto; Xu, Peiyu; Faure, Guilhem; Maguire, Samantha; Kannan, Soumya; Altae-Tran, Han; Vo, Sam; Desimone, AnAn; Macrae, Rhiannon K.; Zhang, Feng (Nature (London), 2023)
RNA-guided systems, which use complementarity between a guide RNA and target nucleic acid sequences for recognition of genetic elements, have a central role in biological processes in both prokaryotes and eukaryotes. For example, the prokaryotic CRISPR–Cas systems provide adaptive immunity for bacteria and archaea against foreign genetic elements. Cas effectors such as Cas9 and Cas12 perform guide-RNA-dependent DNA cleavage 1 . Although a few eukaryotic RNA-guided systems have been studied, including RNA interference 2 and ribosomal RNA modification 3 , it remains unclear whether eukaryotes have RNA-guided endonucleases. Recently, a new class of prokaryotic RNA-guided systems (termed OMEGA) was reported 4 , 5 . The OMEGA effector TnpB is the putative ancestor of Cas12 and has RNA-guided endonuclease activity 4 , 6 . TnpB may also be the ancestor of the eukaryotic transposon-encoded Fanzor (Fz) proteins 4 , 7 , raising the possibility that eukaryotes are also equipped with CRISPR–Cas or OMEGA-like programmable RNA-guided endonucleases. Here we report the biochemical characterization of Fz, showing that it is an RNA-guided DNA endonuclease. We also show that Fz can be reprogrammed for human genome engineering applications. Finally, we resolve the structure of Spizellomyces punctatus Fz at 2.7 Å using cryogenic electron microscopy, showing the conservation of core regions among Fz, TnpB and Cas12, despite diverse cognate RNA structures. Our results show that Fz is a eukaryotic OMEGA system, demonstrating that RNA-guided endonucleases are present in all three domains of life. Fanzor is shown to be an RNA-guided DNA endonuclease, demonstrating that such endonucleases are found in all domains of life and indicating a potential new tool for genome engineering applications.